Critical reading research and its implications for critical reading skills for Indonesian language teachers: A systematic literature review - Arif Setiawan; Nguyen Thi Thu Hang; Fauzan Fauzan; Ganes Tegar Derana (BAHASTRA, 2023)
The abundance of information sources is the result of rapid technological advances. Rapid technological advances must be balanced with reading skills, one of which is critical reading skills used to filter information sources. This systematic literature review aims to compare the findings of research articles published by the Science and Technology Index (SINTA). The keyword used to find articles in the SINTA database is "critical reading." The search results found 78 articles, then 23 articles were selected that met the criteria for analysis. The reporting items selected for the systematic literature review and meta-analysis were the inclusion and exclusion models. In the last ten years, the number of publications dominated in 2016 with six articles. The types of research used by researchers in reviewing critical reading skills are R & D, quantitative, qualitative, and CAR. The research subjects used by the researchers consisted of class X high school students, class VII junior high school students, class VIII junior high school students, fifth-grade elementary school students, and junior high school teachers. The publication and citation structure reveals that, out of 23 articles, they have been cited 114 times, with the 2016 publication having the most citations, a total of 46 times. Writers who have a track record of publications covering critical reading skills are (1) Nuria Reny Hariyati, (2) Hespi Septiana, and (3) Endah Tri Priyatni, all three of whom have a publication track record of 10 articles. The writing institutions are divided into two institutions, namely schools (13%) and colleges (87%), and the collaboration of writers shows a number that is quite far apart, where 14 authors collaborate and nine single authors. There are eight ideas for reflection by Indonesian teachers in teaching critical reading skills.